Detroit's community benefits ordinance: setbacks and opportunities to giving residents a voice in development. Issue 1 (2nd January 2021) - Berglund, Lisa; Butler, Sam
ABSTRACT: In 2016, Detroiters passed a community benefits ordinance with the main goal of having their voices heard in the process of development negotiating a set of benefits that will be delivered at the cost of the developer. To evaluate how effectively this new approach has incorporated the voices of Detroiters into developments, we conducted a qualitative analysis of interviews with residents, developers and planners, and policy documents. We propose several amendments to the Ordinance like more inclusionary selection of residents for negotiations, lengthening the timeline, and removing interference from overlapping agreements that may prevent local communities from winning certain benefits.